2014
DOI: 10.1159/000363104
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma: Differences between Sun-Exposed and Non-Sun-Exposed Variants - A Clinical Analysis of 36 Cases

Abstract: Background: There are few studies focusing on the clinical characteristics of Merkel cell carcinoma (MCC). Objective: To retrospectively analyze the clinical features of our patients and their relationship with sun exposure. Methods: Thirty-six patients diagnosed with MCC (20 men and 16 women, mean age 72.08 years) were included in the study. Results: 21 patients developed MCC in sun-exposed skin and 15 patients in non-sun-exposed areas. MCC was >2 cm in 19 cases. Six of the 7 patients who died as a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
5
0
4
Order By: Relevance
“…The clinical picture is variable and ranges from erythematous plaques to erythematous or pink, sometimes violaceous, sharply demarcated nodules with a smooth and shiny surface. Tumor growth is usually very rapid . The most important clinical features of Merkel cell carcinoma are summarized under the acronym AEIOU: a symptomatic, rapid e xpansion, i mmunosuppression, o lder patient, located on U V‐damaged skin.…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…The clinical picture is variable and ranges from erythematous plaques to erythematous or pink, sometimes violaceous, sharply demarcated nodules with a smooth and shiny surface. Tumor growth is usually very rapid . The most important clinical features of Merkel cell carcinoma are summarized under the acronym AEIOU: a symptomatic, rapid e xpansion, i mmunosuppression, o lder patient, located on U V‐damaged skin.…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…The most common location is head and neck, followed by upper extremities, lower extremities, and trunk. Marcoval et al reported that patients with non-sun-exposed MCC have worse prognosis than those with sun-exposed MCC, and have a greater chance of death by MCC (Marcoval et al, 2014). Although extremely rare, non-sun-exposed MCC is a more malignant variant of MCC.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows non-sun-exposed MCC from the English language literature. Marcoval et al reported that patients with non-sun-exposed MCC have worse prognosis than those with sun-exposed MCC, and have a greater chance of death by MCC (Marcoval et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Das klinische Erscheinungsbild ist variabel und reicht von rötlichen Plaques bis zu rötlichen oder pinkfarbenen, manchmal violetten, scharf begrenzten Knoten mit glatter, glänzender Oberfläche. Zumeist wächst der Tumor sehr rasch . Die wichtigsten klinischen Eigenschaften des Merkelzellkarzinoms werden zusammengefasst unter dem Akronym AEIOU: A symptomatisch, schnelle E xpansion, I mmunsuppression, älterer ( o lder) Patient, Lokalisation auf U V‐geschädigter Haut.…”
Section: Merkelzellkarzinomunclassified